2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8794108
|View full text |Cite
|
Sign up to set email alerts
|

EMG-Controlled Non-Anthropomorphic Hand Teleoperation Using a Continuous Teleoperation Subspace

Abstract: We present a method for EMG-driven teleoperation of non-anthropomorphic robot hands. EMG sensors are appealing as a wearable, inexpensive, and unobtrusive way to gather information about the teleoperator's hand pose. However, mapping from EMG signals to the pose space of a non-anthropomorphic hand presents multiple challenges. We present a method that first projects from forearm EMG into a subspace relevant to teleoperation. To increase robustness, we use a model which combines continuous and discrete predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our experiments in this paper show that the subspace is relevant for at least three different hands, and we would like to continue to show that is relevant for other hands with different kinematic configurations. We have already shown that the teleoperation subspace is suitable for lower dimensional controls, like electromyography (EMG) [37] and would like to validate this control with more kinematic configurations as well. Finally, we would like to show that the subspace is useful for more complex tasks, like assembling and disassembling machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments in this paper show that the subspace is relevant for at least three different hands, and we would like to continue to show that is relevant for other hands with different kinematic configurations. We have already shown that the teleoperation subspace is suitable for lower dimensional controls, like electromyography (EMG) [37] and would like to validate this control with more kinematic configurations as well. Finally, we would like to show that the subspace is useful for more complex tasks, like assembling and disassembling machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of control scheme effectiveness is typically done by comparing user performance across a set of experimenter-designed control schemes on a predefined control interface ( Rosa et al, 2015 ; El-Hussieny et al, 2018 ; Wang et al, 2018 ; Meeker and Ciocarlie, 2019 ). An alternative, more user-centered approach to control scheme design is to base the control scheme off of information acquired from users in the form of survey or motion data ( Li et al, 2020 ; Losey et al, 2020 ; Bobu et al, 2023 ).…”
Section: Related Workmentioning
confidence: 99%
“…Since its first appearance in the '40s (Leon Gillis, 1948), myoelectric control has established itself as an effective mean of controlling artificial limbs. Nowadays, its range of application extends to all those fields of robotics in which humans have to control robots, as teleoperation (Vogel et al, 2011; Meeker and Ciocarlie, 2018), assistive robotics (Song et al, 2008), supernumerary limbs (Hussain et al, 2016; Leigh and Maes, 2016; Ciullo et al, 2018), and of course prosthetics (Segil et al, 2014; Godfrey et al, 2018; i limb, 2018; Michelangelo, 2018; Taska, 2018; Vincent, 2018).…”
Section: Introductionmentioning
confidence: 99%